The Prevent and Reverse Heart Disease Cookbook : Over 125 Delicious, Life-changing, Plant-based Recipes - Esselstyn, Ann Crile; Esselstyn, Jane; Esselstyn, Caldwell B., 1933- (New York : Avery, a member of Penguin Group (USA), 2014)
"The long-awaited cookbook companion to the revolutionary New York Times bestseller Prevent and Reverse Heart Disease. President Bill Clinton is just one of the more than 336,000 readers who have benefited from Caldwell B. Esselstyn's bestseller, Prevent and Reverse Heart Disease. The plant-based nutrition plan that Dr. Esselstyn advocates based on his twenty-year nutritional study-the most comprehensive of its kind-is proven to stop and reverse even advanced coronary disease. Ann Crile Esselstyn and Jane Esselstyn are a mother-daughter team with decades of experience developing delicious, healthful dishes for both their family and Dr. Esselstyn's many grateful patients. In this much-anticipated cookbook, they share more than 125 delicious and nutritious recipes that make it easy to follow Dr. Esselstyn's lifesaving dietary advice. Heart disease remains one of today's deadliest killers, and The Prevent and Reverse Heart Disease Cookbook empowers readers to make their hearts healthier, one delectable meal at a time"--
"Ann and Jane Esselstyn present the long-awaited cookbook companion to Prevent and Reverse Heart Disease, the bestselling handbook on reversing heart disease through diet, with a foreword from its author Caldwell B. Esselstyn, and offer over 125 delicious plant-based oil-and-nut- free recipes guaranteed to make you heart-attack proof in a beautiful produced four-color book"--
Keywords: Coronary heart disease -- Recipes -- Diet therapy; Coronary heart disease -- Prevention; Vegetarian cooking; Natural foods; COOKING / Health & Healing / Heart; COOKING / Vegetarian & Vegan; HEALTH & FITNESS / Diseases / Heart; Cookbooks